EFFECT OF NANOFERTILIZERS AND APPLICATION METHODS ON VEGETATIVE GROWTH AND YIELD OF DATE PALM - & Ahmed, Jubeir (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this study is to investigate the effect of nano fertilizers and application method on growth and yield of date palm. The experiment was carried out at AL- Rabeaa date palms station - Department of Horticulture - Ministry of Agriculture on 10 years old of Khastawi date palm cultivar during 2016 - 2017. Factorial experiment (3×6) within randomized complete block design with three replications .carried out using two factors: the first was three application methods; foliar application, injection with trunk and soil fertilization (A1, A2, A3) respectively. The second factor was different types of fertilizer, seaweed extract of the nanotechnology product with two concentrations: first (F1) (1,0.5,2)ml.L-1and the second (F2) (2,1,4) ml.L-1 respectively, depending on the method of application and optimus-plus fertilizer the product of nanotechnology with two concentrations: first (F3) (1,0.5,2) ml.L-1 and the second (F4) (2,1,4) ml.L-1 respectively depending on the method of application also used NPK fertilizers (F5) (2,1,4) g.L-1 and control treatment (F0).The results showed that treatment (F1) was increased fruit weight (5.26 g). While (F2) produced 36.75 kg yield. The highest percentage of maturity appeared in (F3) (73.56%). Treatments F4 and F5 showed an increase of amino acids in fruits (9.68 and 10.88 mg-1 dry weight).injection treatment superior in the percentage of dry matter in leaves (38.60%), chlorophyll content (32.19 mg, 100 g-1),and yield (36.07 kg). we could be concluded that using nutrients and injection fertilizer improved vegetative growth and increase yield of date palm.